Adsorption of Some Industrial Pollutants from their Aqueous Solutions - Mohsen, Dafer Rafeed Qasim; Alwan, Liqaa Hussein (American Journal of Bioscience and Clinical Integrity, 2025)
This study investigates the adsorption of Malachite Green (MG) dye from aqueous solutions using activated charcoal. UV–Visible spectroscopy at 424 nm was used to determine removal efficiency. Batch experiments examined the influence of contact time, adsorbent mass, and temperature. Optimal conditions were found at a dye concentration of 25 ppm, 0.05 g of adsorbent, and 20 minutes of contact time. Removal efficiency increased with time until equilibrium, indicating gradual occupation of adsorption sites. Adsorption isotherms were analyzed using Langmuir, Freundlich, and Temkin models. The data fit well with Freundlich and Temkin models, suggesting heterogeneous surface adsorption, while the Langmuir model showed poor correlation. Thermodynamic parameters (ΔG, ΔH, ΔS) were determined at 293–313 K. Negative ΔG values at all temperatures indicated spontaneous adsorption, while the negative ΔH (< 40 kJ/mol) suggested an exothermic and physical adsorption process.Kinetic analysis revealed that the pseudo-second-order model best described the adsorption behavior, indicating chemisorption predominance. Overall, activated charcoal demonstrated high efficiency in removing MG dye, supported by favorable kinetic, thermodynamic, and isotherm data, suggesting its suitability for industrial wastewater treatment applications.